Sensitivity analysis on natural convective trapezoidal cavity containing hybrid nanofluid with magnetic effect: Numerical and statistical approach - Sweety Khatun; Rupa Kundu; Saiful Islam; Ritu Aktary; Dipankar Kumar (Heliyon)
The numerical analysis examines the attributes of magnetohydrodynamic natural convection in a closed cavity including a circular hollow. Because mono and hybrid nanofluids have many applications in thermal engineering and manufacturing, hybrid nanofluids are utilized as the substance within the entire domain. The investigation centers on a closed, trapezoidal-shaped hollow with a heated surface ring. The inclined vertical walls are treated as cold exteriors, while the others are insulated. Another factor is taking a magnetic field horizontally to the cavity. The entire cavity contains a hybrid nanofluid, an amalgamation of SiO2 and Ag nanoparticles with water. The associated governing equations are simulated via the finite element method. Exploiting streamlines, isotherms, and line graphs, the results are physically explained for a range of values of Rayleigh number (103 ≤ Ra ≤ 106), nanoparticle volume fraction (0 ≤ ϕ ≤ 0.1), and Hartmann number (0 ≤ Ha ≤ 100). The RSM is used to display 2D and 3D effects of significant factors on response function. A best-fitted correlation is built up to examine the rate of sensitivity. It is found that incorporating hybrid nanoparticles and intensifying the Rayleigh number directs to the thermal actuation of hybrid nanofluid. In the event of a growing magnetic impact, reverse behaviors should be noted. The water's ability to transmit heat increases to 11.29 % when the Ag-SiO2-H2O hybrid nanofluid is used. The imposition of a magnetic field (Ha = 25), the rate of heat transmission lessens to 2.4 %. The Ra has positive sensitivity whereas Ha shows inverse behavior. Lastly, the study's findings might guide designing a successful natural convective mechanical device.